U.S. Army Cold Regions Research and Engineering Laboratory (2006)
The Cold Regions Research and Engineering Laboratory is a facility of the U.S. Army Corps of Engineers that addresses the problems and opportunities unique to the world's cold regions through scientific and engineering research.